2018
DOI: 10.1096/fj.201800382rr
|View full text |Cite
|
Sign up to set email alerts
|

Nogo‐A promotes inflammatory heat hyperalgesia by maintaining TRPV‐1 function in the rat dorsal root ganglion neuron

Abstract: Nogo-A is a key inhibitory molecule of axon regeneration in oligodendrocytes. However, little is known about its role in adult neurons. In this study, we showed an important function of Nogo-A on regulation of inflammatory pain in dorsal root ganglion (DRG) neurons. In adult rats with complete Freund's adjuvant (CFA) hind paw inflammation, DRG neurons showed a significant increase in Nogo-A expression. Disruption of Nogo-A signaling with Nogo-66 receptor antagonist peptide, Nogo-A blocking antibody, Nogo-A sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(52 citation statements)
references
References 48 publications
(72 reference statements)
2
50
0
Order By: Relevance
“…Some studies have reported that apoptosis is involved in neurotoxicity or pain [28][29][30], which coincides with our findings of significant enrichment of the negative regulation of the neuron apoptotic process (GO:0043524, p value � 1.212e − 02) and negative regulation of the apoptotic process (GO:0043066, p value � 1.628e − 02). Moreover, the FoxO signaling pathway (rno04068, p value � 4.735e − 02) and MAPK signaling pathway (rno04010, p value � 4.672e − 02) were also significantly enriched.…”
Section: Discussionsupporting
confidence: 92%
“…Some studies have reported that apoptosis is involved in neurotoxicity or pain [28][29][30], which coincides with our findings of significant enrichment of the negative regulation of the neuron apoptotic process (GO:0043524, p value � 1.212e − 02) and negative regulation of the apoptotic process (GO:0043066, p value � 1.628e − 02). Moreover, the FoxO signaling pathway (rno04068, p value � 4.735e − 02) and MAPK signaling pathway (rno04010, p value � 4.672e − 02) were also significantly enriched.…”
Section: Discussionsupporting
confidence: 92%
“…A purified rabbit polyclonal antibody (IgG) of Nogo‐A aa 846‐861 was made using immunoaffinity purification by AbMax Biotechnology Co., LTD (Beijing, China). Nogo‐A antibody or normal rabbit IgG (sc‐2028, Santa Cruz Biotechnology, CA, USA) (prepared in a concentration of 0.2 μg/μL) was injected intrathecally in a volume of 3 μL 27 . Half hour after the injection of peptide or antibody, 25% of CFA was injected.…”
Section: Methodsmentioning
confidence: 99%
“…Nogo-A antibody or normal rabbit IgG (sc-2028, Santa Cruz Biotechnology, CA, USA) (prepared in a concentration of 0.2 μg/μL) was injected intrathecally in a volume of 3 μL. 27 Half hour after the injection of peptide or antibody, 25% of CFA was injected. Nociceptive responses were measured 1, 2, 6, and 24 hours after CFA administration.…”
Section: Intrathecal Injection Of Peptides and Antibodymentioning
confidence: 99%
See 2 more Smart Citations